LEVERAGE, INSTITUTIONAL OWNERSHIP, AND FIRM SIZE ON TAX AVOIDANCE: PROFITABILITY AS A MEDIATING VARIABLE - Nur Fitria Sani; Ranidhan Putri; Selica Vianes; Hakim, Mohamad Zulman; Ahmad Jayanih; Ahmad Zaki Mubarok (ZILLZELL MEDIA PRIMA, 2025)
This study aims to examine the effect of leverage, institutional ownership, and company size on tax avoidance with profitability as an intervening variable in energy sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The population of this study includes all manufacturing companies in the energy sector, with a sample of 70 companies selected using purposive sampling techniques. This research method uses a quantitative approach with panel data regression analysis based on Eviews 12 Student Version software. The F test shows that leverage, institutional ownership, company size, and profitability simultaneously have a significant effect on tax avoidance, with an F-count value of 1.862133 and a probability value of 0.044307 (p <0.05). T-test shows that leverage (t-count = 0.132247; p = 0.2688), institutional ownership (t-count = -0.639379; p = 0.5254), and firm size (t-count = 1.362275; p = 0.1790) do not have a significant effect on tax avoidance. In contrast, profitability (t-count = -3.083855; p = 0.0033) has a significant negative effect on tax avoidance. Testing with the Sobel test shows that profitability cannot mediate the effect of leverage and institutional ownership on tax avoidance. However, profitability can mediate the negative effect of firm size on tax avoidance. This finding supports the Agency Theory, which states that profitability can influence management decision making in managing tax burdens.